Collaborating Across the Departments of Veterans Affairs and Defense to Integrate Mental Health and Chaplaincy Services - Nieuwsma, Jason A. (J Gen Intern Med, 2014)
BACKGROUND: Recognizing that clergy and spiritual care providers are a key part of mental health care systems, the Department of Veterans Affairs (VA) and Department of Defense (DoD) jointly examined chaplains’ current and potential roles in caring for veterans and service members with mental health needs. OBJECTIVE: Our aim was to evaluate the intersection of chaplain and mental health care practices in VA and DoD in order to determine if improvement is needed, and if so, to develop actionable recommendations as indicated by evaluation findings. DESIGN: A 38-member multidisciplinary task group partnered with researchers in designing, implementing, and interpreting a mixed methods study that included: 1) a quantitative survey of VA and DoD chaplains; and 2) qualitative interviews with mental health providers and chaplains. PARTICIPANTS: Quantitative: the survey included all full-time VA chaplains and all active duty military chaplains (n = 2,163 completed of 3,464 invited; 62 % response rate). Qualitative: a total of 291 interviews were conducted with mental health providers and chaplains during site visits to 33 VA and DoD facilities. MAIN MEASURES: Quantitative: the online survey assessed intersections between chaplaincy and mental health care and took an average of 37 min to complete. Qualitative: the interviews assessed current integration of mental health and chaplain services and took an average of 1 h to complete. KEY RESULTS: When included on interdisciplinary mental health care teams, chaplains feel understood and valued (82.8–100 % of chaplains indicated this, depending on the team). However, findings from the survey and site visits suggest that integration of services is often lacking and can be improved. CONCLUSIONS: Closely coordinating with a multidisciplinary task group in conducting a mixed method evaluation of chaplain-mental health integration in VA and DoD helped to ensure that researchers assessed relevant domains and that findings could be rapidly translated into actionable recommendations.